2021
DOI: 10.1075/lab.20076.wes
|View full text |Cite
|
Sign up to set email alerts
|

Variable V2 in Norwegian heritage language

Abstract: This paper discusses possible attrition of verb second (V2) word order in Norwegian heritage language by investigating a corpus of spontaneous speech produced by 50 2nd–4th generation heritage speakers in North America. The study confirms previous findings that V2 word order is generally stable in heritage situations, but nevertheless finds approximately 10% V2 violations. The cases of non-V2 word order are argued to be due to lack of activation of the heritage language grammar, making it vulnerable to crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
5
4
0
Order By: Relevance
“…We have observed 1.8% V2 violations in AmSw. A similar frequency has been noted for AmNo; Westergaard et al (2021) find 2.2% non-V2 in declaratives in the Norwegian part of CANS (N = 10.609). Some of these examples could, however, be interpreted as base-generated adjuncts (HTLD), possibly making the frequencies even more similar.…”
Section: V2-violations-attrition and CLIsupporting
confidence: 82%
See 3 more Smart Citations
“…We have observed 1.8% V2 violations in AmSw. A similar frequency has been noted for AmNo; Westergaard et al (2021) find 2.2% non-V2 in declaratives in the Norwegian part of CANS (N = 10.609). Some of these examples could, however, be interpreted as base-generated adjuncts (HTLD), possibly making the frequencies even more similar.…”
Section: V2-violations-attrition and CLIsupporting
confidence: 82%
“…Previous studies of heritage Scandinavian in North America have also shown evidence of considerable stability (see Westergaard et al 2021 on AmNo; Kühl and Petersen 2018 on American Danish). These studies have not considered left dislocation, but Bousquette et al (2021) show some examples of CLD in AmNo, and we can easily find additional attestations in the AmNo part of CANS: Although the overall tendency in the C-domain in AmSw is stability, we have observed some differences between the heritage variety and the homeland baseline: there are scattered examples of non-V2 of a type that does not occur in the homeland variety, and there is an increase in the frequency of SV-order.…”
Section: The American Swedish C-domainmentioning
confidence: 89%
See 2 more Smart Citations
“…See alsoWestergaard, Lohndal & Lundquist (2021) for evidence of the relationship between the production of non-subject-initial declaratives and V2 errors in heritage speakers of Norwegian living in the USA.…”
mentioning
confidence: 99%